2007
DOI: 10.1021/jp0686994
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Vibrational Spectroscopic Studies of the Adsorption and Speciation of Nitric Acid at the Vapor/Acid Solution Interface

Abstract: Nitric acid plays an important role in the heterogeneous chemistry of the atmosphere. Reactions involving HNO(3) at aqueous interfaces in the stratosphere and troposphere depend on the state of nitric acid at these surfaces. The vapor/liquid interface of HNO(3)-H2O binary solutions and HNO(3)-H(2)SO(4)-H2O ternary solutions are examined here using vibrational sum frequency spectroscopy (VSFS). Spectra of the NO2 group at different HNO(3) mole fractions and under different polarization combinations are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…In bulk water, nitrate is surrounded by a solvent cage that facilitates both the recombination of the NO 2 and OH radicals produced by reaction and their deactivation by collision with solvent molecules, thus decreasing the photolysis quantum yield. ,,, MD simulations have shown that when halide anions (especially bromide) are present, nitrate ions are dragged closer to the interface so that the water solvent cage surrounding them is reduced, , arguably making the escape of NO 2 to the gas phase easier. ,, Nevertheless, despite the large amount of work done on nitrate photochemistry, open issues remain that are not yet completely understood. For instance, it was recently shown that an important part of nitric acid remains undissociated at the air–water interface, , and the relevance of the corresponding photochemistry is still undetermined.…”
Section: Photochemistry Of Oh Precursorsmentioning
confidence: 99%
“…In bulk water, nitrate is surrounded by a solvent cage that facilitates both the recombination of the NO 2 and OH radicals produced by reaction and their deactivation by collision with solvent molecules, thus decreasing the photolysis quantum yield. ,,, MD simulations have shown that when halide anions (especially bromide) are present, nitrate ions are dragged closer to the interface so that the water solvent cage surrounding them is reduced, , arguably making the escape of NO 2 to the gas phase easier. ,, Nevertheless, despite the large amount of work done on nitrate photochemistry, open issues remain that are not yet completely understood. For instance, it was recently shown that an important part of nitric acid remains undissociated at the air–water interface, , and the relevance of the corresponding photochemistry is still undetermined.…”
Section: Photochemistry Of Oh Precursorsmentioning
confidence: 99%
“…At the molecular level, the changes in p K a are attributed to the preferential partitioning of neutral species at the air–water interface due to the energy cost associated with ions that are less solvated at the interface. Understanding local surface solvation effects and their impact on p K a is especially important, in part due to the key role that acidic and basic aqueous solutions play in environmental and atmospheric chemistry. Additionally, surface p K a impacts interfacial biochemical phenomenon, such as protein folding and unfolding, owing to the pH dependence of amino acid protonation/deprotonation…”
Section: Introductionmentioning
confidence: 99%
“…VOCs affect hydroxyl (OH) radical and ozone formation and oxidation processes (Jacob et al, 2005; Hüve et al, 2007). Ozone formation in photochemical reactions requires NOx and reactive VOCs (Crutzen, 1979; Logan, 1985), and for this reason, it is important to quantify seasonal VOC emission fluxes from different sources. These sources should be quantified more accurately, because several studies have shown that measured and modeled ozone deposition fluxes and OH radical reactivities include significant differences (Mogensen et al, 2011; Wolfe et al, 2011; Rannik et al, 2012; Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%